Beneficial effects of small-sided games as a conclusive part of warm-up routines in handball - Iacono, A. D.; Vigotsky, A. D.; Laver, L.; Halperin, I. (SportRxiv, 2018)
The aim of this study was to compare the effects of small sided games (SSG) and traditional warm-up strategies on the mechanical, physiological, and perceptional responses of handball players. Using a randomized and counterbalanced design, 12 elite male handball players completed a general 8 min warm-up which was concluded with an 8 min section of either specific handball shooting drills or 3 × 2 min of SSG with a passive recovery of 1 min between bouts. Countermovement jumps and plyometric press-ups were assessed before and immediately after the warm-up regimens using a force plate. Heart rate (HR) was assessed during the warm up regimens, and rating of perceived effort (RPE) was assessed after the regimens. Meaningful differences favoring SSG were observed in most of the kinetic variables in the countermovement jumps and plyometric press-ups (|Hedges` g| = 0.26-1.42). Conversely, no meaningful differences were found between warm up regimens in RPE or HR responses (z-scores = 0.45 and 1.88, respectively). These results indicate that concluding warm-ups with SSGs offer greater benefits compared to a more traditional warm-up routine, despite similar HR and RPE responses even when matched for duration among elite level handball players.